2007
DOI: 10.1001/jama.297.20.2197-c
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Prevention Measures in Coalition Troops in Afghanistan

Abstract: 1 found that treatment with statins was associated with regression of coronary atherosclerosis (assessed by intravascular ultrasonography) when low-density lipoprotein cholesterol (LDL-C) was substantially reduced and high-density lipoprotein cholesterol (HDL-C) was increased by more than 7.5%. The authors state that it remains to be determined whether these changes translate to improved clinical outcomes because the small increases in HDL-C observed during statin therapy have never been shown to correlate wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…A report 24 in 2006 indicated that the US government provides "treated uniforms" and "repellant" as part of its non-drug malaria prevention measures to troops deployed to Afghanistan. Also, survey information concerning MSMs participation in DOT programs would also have provided additional insight into compliance.…”
Section: Discussionmentioning
confidence: 99%
“…A report 24 in 2006 indicated that the US government provides "treated uniforms" and "repellant" as part of its non-drug malaria prevention measures to troops deployed to Afghanistan. Also, survey information concerning MSMs participation in DOT programs would also have provided additional insight into compliance.…”
Section: Discussionmentioning
confidence: 99%
“…1 Suppressive chemoprophylaxis was implemented by most of the ISAF forces, and mefloquine was the generally preferred agent. 2 This Figure 1 Afghanistan provinces can be clustered into three groups with different risk levels of malaria. 3 The risk is, however, far from being homogeneous within each province; transmission occurs mainly in river valleys where rice fields are common.…”
mentioning
confidence: 99%
“…Contrary to this a retrospective study of personnel deployed to Iraq showed that 81% of those offered AMC accepted it [7]. There have been several reported cases of non-UK soldiers returning from Afghanistan who have become infected with Plasmodium Vivax [8,9], which if untreated could cause significant morbidity and occasionally lead to death [10,11]. Although we are unable to report on the malaria infection rate in UK forces that have deployed to Afghanistan, and we are unaware of malarial infection in the casualties included in this investigation, we believe that it may be appropriate to re-evaluate whether a country wide antimalarial prescription is necessary.…”
Section: Discussionmentioning
confidence: 93%